Towards establishing a training programme for increasing teachers' awareness of higher order thinking skills: A preliminary survey of the state of affairs - Abdul Karim, Abdul Malek; Abdullah, Mohd Nordin; Mohd Yusoff, Nurahimah; Abdullah, Syaharom (Universiti Utara Malaysia, 1997)
Teachers play a pivotal role in transforming the classroom into an active, inquisitive environment that may foster the development of more effective thinking in students. Teachers classroom behaviour has great influence on students as teacher modelling is believed to be a powerful means for encouraging the development of appropriate behaviour as well as attitudes towards thinking. The present study was conducted to verify the practicality and needs of conducting a comprehensive evaluation of the teaching of thinking in secondary schools. It tried to ascertain teachers' disposition towards the teaching of thinking, the extent of direct and indirect teaching of thinking, and the underlying influence of public examination on instruction. The questionnaire survey method and observation were employed to gather data. Ten randomly selected schools and 70 English language teachers were used. The data gathered seem to suggest the existence of discrepancy between respondents' responses to the questionnaire and actual classroom teaching - the positive disposition was not reflected in classroom practice. The data gathered also indicate that teachers believed that content knowledge bears on performance in public examination. Though the evidence was compelling, the study was limited in scope. A comprehensive study is, therefore, recommended in order to gather more conclusive evidence about the current state of affairs.